The Maga’s rape: study of the description of rape in literature from the case of Rayuela written by Julio Cortázar - Gutiérrez Contreras, María Verónica (Re-presentaciones: Periodismo, comunicación y sociedad, 2022)
The sexual abuse that La Maga suffered as a child is so much more than just a story in a book. It is about maintaining the discrimination and underestimation of this sort of aggression that most women suffer around the world. This work examines the stories of sexual assaults in fiction through the analysis of this specific chapter of Rayuela written by Julio Cortázar